2011
DOI: 10.1038/jp.2011.115
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity, prematurity, birth weight and pregnancy loss: a prospective cohort study at four primary health center areas of Karnataka, India

Abstract: Objective: To determine whether consanguinity adversely influences pregnancy outcome in South India, where consanguinity is a common means of family property retention.Study Design: Data were collected from a prospective cohort of 647 consenting women, consecutively registered for antenatal care between 14 and 18 weeks gestation, in Belgaum district, Karnataka in 2005. Three-generation pedigree charts were drawn for consanguineous participants. w 2 -Test and Student's t-test were used to assess categorical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In their study, PTB was also not increased among consanguineous marriages. Similar findings of a lack of correlation between consanguinity and PTB were also noted in India and Turkey [15][16][17] . However, in these studies the authors did not distinguish between spontaneous and medically induced PTB, and the sample sizes were relatively small.…”
Section: Ptb In Consanguineous Marriagessupporting
confidence: 69%
“…In their study, PTB was also not increased among consanguineous marriages. Similar findings of a lack of correlation between consanguinity and PTB were also noted in India and Turkey [15][16][17] . However, in these studies the authors did not distinguish between spontaneous and medically induced PTB, and the sample sizes were relatively small.…”
Section: Ptb In Consanguineous Marriagessupporting
confidence: 69%
“…Congenital anomalies represented 8.4% of all causes, with Belagavi, India having a substantially higher proportion (nearly 20%) due to congenital anomalies. A prior study conducted at this site in India found 24% of pregnant women were in consanguineous partnerships, which is a high risk for birth defects . Finally, in this study, prematurity was responsible for nearly 7% of all stillbirths.…”
Section: Discussionsupporting
confidence: 50%
“…A meta-analysis of 46 studies on consanguinity and links to early deaths showed a statistically significant 1.3 % higher number of infant deaths in children of first cousins than those born to non-consanguineous couples (Bittles 2012). Stillbirths were also higher by 0.5 % in first cousin progeny (Bittles 2012), and recent data continue to show increased stillbirths (Bellad et al 2012;Sørbye et al 2014) as well as increased infant deaths (Charafeddine et al 2012;Sørbye et al 2014) in children of consanguineous parents compared to non-consanguineous couples.…”
Section: The Research Sitementioning
confidence: 99%